2020
DOI: 10.1016/j.optlastec.2019.105898
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort pulse propagation through depressed-cladding channel waveguides in YAG crystal: Spatio-temporal characterization

Abstract: Inscription of optical waveguides by direct femtosecond laser irradiation has become a very versatile tool for the development of integrated photonic devices, such as waveguide lasers, frequency converters or photonic lanterns, among many others. The potential application of such devices for the control and manipulation of ultrashort pulses requires the precise knowledge of the temporal distortions that may be induced in the pulse propagation. Currently, research in this topic is scarce, and to our knowledge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…These laser tracks serve as either beam blockers or confiners that reshape the intensity profile of the propagating guided field over a gradually varied or a multi-element assembled configuration. At the expense of more complicated designs and longer fabrication time, photonic-lattice-like cladding waveguides exhibit a designable feature for beam manipulation in a 3D manner, which paves a way to construct compact optical devices based on a wide range of optical crystals [51][52][53][54][55][56] . Furthermore, it has been found that the amount of the track lattice layers is an important factor for light field restriction: multi-layer track lattice offers better light confinement than a single-layer structure 49 .…”
Section: Multi-linementioning
confidence: 99%
“…These laser tracks serve as either beam blockers or confiners that reshape the intensity profile of the propagating guided field over a gradually varied or a multi-element assembled configuration. At the expense of more complicated designs and longer fabrication time, photonic-lattice-like cladding waveguides exhibit a designable feature for beam manipulation in a 3D manner, which paves a way to construct compact optical devices based on a wide range of optical crystals [51][52][53][54][55][56] . Furthermore, it has been found that the amount of the track lattice layers is an important factor for light field restriction: multi-layer track lattice offers better light confinement than a single-layer structure 49 .…”
Section: Multi-linementioning
confidence: 99%